Development of methods and technologies for creating intelligent scientific and educational internet resources - Ardak G. Batyrkhanov; Zhanna B. Sadirmekova; Madina A. Sambetbayeva; Assel N. Nurgulzhanova; Zhuldyz S. Ismagulova; Aigerim S. Yerimbetova (Bulletin of Electrical Engineering and Informatics, 2022)
The purpose of this work is to develop methods, technologies and tools for creating and maintaining intelligent scientific and educational internet resources (ISEIR) based on a service-oriented approach and Semantic Web technologies. The main purpose of ISEIR is to provide meaningful access to scientific and educational information resources of a given field of knowledge and integrated information processing services. According to the preliminary concept, an intelligent scientific and educational internet resource will be an information system accessible via the internet which provides ontology-based systematization and integration of scientific knowledge, data and information resources into a single information space together with a meaningful effective access to them as well as supporting their use in solving various scientific and educational tasks. ISEIR is equipped with an ergonomic web-based user interface and special editors designed to manage the knowledge integrated into it. The proposed approach to the construction of intelligent scientific and educational internet resources is the basis for the developed technology in creating and maintaining information environments for distributed learning.